Collective Requirements of the Students in Large Multilevel Intermediate English Classes: A Quantitative Study (Journal of Social Sciences Review, 2023)
Large classes are, by definition, diverse and multilevel, indicating differences among the students, including their aptitude for learning a language, traditional background, styles of learning, age, language attitude, domestic language, cultural experiences, motivational level, etc. Therefore, the study aimed to investigate the collective requirements of the students in large multilevel intermediate English classes. The percentage of the students’ responses was analyzed in the study, so the study was exploration-type. All the intermediate students of the Government Post Graduate College Okara were the population of the study. The purposive non-random sampling procedure was adopted to select the sample from the population. The data was collected from the 120 intermediate levels English students of the College. The results of the study showed that the percentage, greater in number, of the large multilevel students who wanted classroom management, collaboration, range of tasks, feedback, English language environment in the classroom, and home assignments. It was recommended that the govt. Should facilitate the instructional process keeping in mind the collective requirements of the large multilevel students.
Keywords: Collective Requirements; Students; Large Classes; Multilevel Students